Effect of Temperature on Li Electrodeposition Behavior in Room-Temperature Ionic Liquids Comprising Quaternary Ammonium Cation. Issue 13 (1st January 2019) - Sano, Hikaru; Kitta, Mitsunori; Shikano, Masahiro; Matsumoto, Hajime
Abstract : Secondary batteries with Li metal anodes have attracted considerable research attention as power sources for electric vehicles. However, the widespread application of these batteries is hindered by short circuiting due to Li dendrite formation, which highlights the need for a more detailed mechanistic understanding of this process. Typical Li-metal-based secondary batteries contain organic solvents, which are unstable under harsh cathodic conditions (i.e., at the Li redox potential), and therefore, decompose to form surface films. Conversely, room-temperature ionic liquids comprising quaternary ammonium cations (QA-RTILs) are very stable under these conditions and are thus considered promising alternatives to the commonly used carbonate solvents, as has been demonstrated in our previous studies. Herein, we investigate the effect of temperature on Li electrodeposition behavior in a selected QA-RTIL, revealing that this behavior is mainly determined based on the deposition overpotential and the Li diffusion coefficient.